The Silent Extinction of Species and Taxonomists—An Appeal to Science Policymakers and Legislators - Ivan Löbl; Bernhard Klausnitzer; Matthias Hartmann; Frank-Thorsten Krell (Diversity, 2023)
The science of taxonomy, albeit being fundamental for all organismic research, has been underfunded and undervalued for about two generations. We analyze how this could happen, particularly in times of a biodiversity crisis, when we have increased awareness amongst the population and decision makers that knowledge about species we share the planet with is indispensable for finding solutions. We identify five major issues: the habit of holding taxonomy in low esteem; the focus on inappropriate publication metrics in evaluating scientific output; the excessive focus on innovative technology in evaluating scientific relevance; shifting priorities in natural history museums away from their traditional strengths; and changing attitudes towards specimen collecting and increasing legislation regulating collecting and international exchange of specimens. To transform taxonomy into a thriving science again, we urgently suggest significantly increasing baseline funding for permanent positions in taxonomy, particularly in natural history museums; reviving taxonomic research and teaching in universities at the tenured professor level; strongly increasing soft money for integrative taxonomy projects; refraining using journal-based metrics for evaluating individual researchers and scientific output and instead focusing on quality; installing governmental support for open access publishing; focusing digitizing efforts to the most useful parts of collections, freeing resources for improving data quality by improving identifications; requiring natural history museums to focus on collection-based research; and ending the trend of prohibitive legislation towards scientific collecting and international exchange of taxonomic specimens, and instead building legal frameworks supportive of biodiversity research.